The Mediterranean Port Economy The cases of Marseille and Mersin - Merk, Olaf (OECD Publishing, 2014)
Ports are no longer perceived as main drivers of urban economic development. A variety of factors have been identified in the academic literature to contribute to urban economic growth, ranging from human capital, entrepreneurial culture, diversity and infrastructure to planning and governance. Port infrastructure is in many cases not even considered as a potential source of economic development. Whereas efficient ports have contributed to a substantial reduction in transportation costs, and thus stimulated external trade and related economic development, the general perception is that most of the gains of external trade have spread out to other regions than the port area or the port region (e.g. Gripaios and Gripaios, 1995). This is related to de-concentration of logistics activity and "port regionalisation" tendencies (Notteboom and Rodrigue, 2005). In contrast, negative impacts related to ports have unevenly affected port-cities, including socio-economic impacts related to a unskilled workforce needed to sustain a port-industrial complexes that have ceased to be labour-intensive. Economic benefits of ports were less ambiguous in the past, when port-cities dominated trade-oriented emerging capitalist economies, as eloquently described in Braudel (1979)
Keywords: Transport; France